2006
DOI: 10.1002/hep.21225
|View full text |Cite
|
Sign up to set email alerts
|

A double-blind randomized trial of adefovir dipivoxil in Chinese subjects with HBeAg-positive chronic hepatitis B

Abstract: Four hundred and eighty Chinese subjects with hepatitis B e antigen (HBeAg)-positive chronic hepatitis B (CHB) were enrolled in a multicenter, double-blind, randomized, placebo-controlled study of adefovir dipivoxil (ADV) 10 mg once daily. There was a significant difference in reduction of serum hepatitis B virus (HBV) DNA after 12 weeks between subjects who received ADV and those who received the placebo (3.4 and 0.1 log 10 copies/mL, respectively, P < .001). Further reductions in serum HBV DNA and increases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
42
1
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 22 publications
4
42
1
1
Order By: Relevance
“…Multinational placebo-controlled clinical trials in HBeAg-positive and negative subjects showed biochemical, virological, and histological improvement. A 52-week ADV treatment resulted in 20% seroclearance of HBeAg, 28% clearance of serum HBV-DNA and 79% with ALT normalization in Chinese cohort (Zeng et al 2006). In this study, our data showed that HBV-DNA seroclearance (41.8% vs 34.6%, p < 0.05) and HBV-DNA reduction (3.6log 10 vs 3.1log 10 , p < 0.05) were significantly higher in genotype B than those in genotype C at week 48 on ADV therapy.…”
Section: Discussionmentioning
confidence: 87%
“…Multinational placebo-controlled clinical trials in HBeAg-positive and negative subjects showed biochemical, virological, and histological improvement. A 52-week ADV treatment resulted in 20% seroclearance of HBeAg, 28% clearance of serum HBV-DNA and 79% with ALT normalization in Chinese cohort (Zeng et al 2006). In this study, our data showed that HBV-DNA seroclearance (41.8% vs 34.6%, p < 0.05) and HBV-DNA reduction (3.6log 10 vs 3.1log 10 , p < 0.05) were significantly higher in genotype B than those in genotype C at week 48 on ADV therapy.…”
Section: Discussionmentioning
confidence: 87%
“…Dose mais elevada de ADV (30mg) demonstrou resultados terapêuticos melhores que dose de 10mg, entretanto foram observados níveis de creatinina maiores que 0,5mg/ dL para a dose de 30mg (8%). O perfil de segurança do ADV foi semelhante ao placebo 7,13 .…”
Section: Adefovir Dipivoxilunclassified
“…In addition, the long-term efficacy of lamivudine is limited by the frequent emergence of drug-resistant HBV mutants [5][6][7]. Adefovir is a nucleotide analogue associated with a low frequency of resistance; however, its antiviral efficacy is not optimal [8,9].…”
mentioning
confidence: 99%